Gambaran Pola Makan Dan Dukungan Keluarga Penderita Diabetes Melitus Yang Menjalani Rawat Jalan Di RSU Dr. Pirngadi Medan Tahun 2015 - Tengku Mirandan Rizky; Ernawati Nasution; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Diabetes Melitus (DM) is a kind of degenerative disease which is still a public health problems in Indonesia. The risk factor which caused by DM disease is an unbalanced diet and individual factor which is family support to the DM patients. This research is to find out the describe of diet and family support for DM patients which are not hospitalized. This research is a survey research with cross sectional design with a sample is DM patients who is not hospitalized in RSU Dr.Pirngadi Medan as many as 100 persons were obtained by accidental sampling. The data which used is a primary data obtained through interview by using 24 hours food recall form, food frequency form and supporting family questioner, beside of primary data also using secondary data were obtained from medical records of RSU Dr.Pirngadi Medan. In research the characteristics of patient mostly aged 51-60 years old, female. Energy intake, carbohydrate, protein and cholesterol for DM patients generally falls in under category which is not appropriate. The meal time of those patient diabetes melitus should more than 3 hours. Family support is good 44% with an appropriate diet and lack of family support is 54,1% with a food pattern is not appropriate. Recommended to health care raise of service the information to patient with diabetes melitus so as to more discipline admission of food pattern, and to the patient with diabetes melitus so as comply food pattern as requested, so that they can develop good habits and focused on the health living. Key words : food pattern, family support, DM patient.